Deteriorated solar panel detection technique of SST for a solar farm application - Khemmook, Panya; Khomfoi, Surin; Phophongviwat, Teeraphon; Pairindra, Worapong (My University, 2019)
This proposed paper introduces the fault detection method for solar cell with Box Plot technique on the Solid State Transformer (SST) for the solar farm application. The Box Plot technique with inclusive quartile value is functioned for finding the upper and lower limit for data analysis. Normally, the fault detections of solar panels are found by using the PV string current from the SST to calculate the upper and lower limit of the Box Plot. If one of the string currents is in the specific outer boundary, therefore, the solar panels are in non-operational condition mode. Generally, the fault detection testing for the solar panels can be categorized in 5 cases: normal condition, open circuit condition, line-line condition, partial shading condition and degradation condition. Finally, based on the simulation result and the actual results, the Box Plot is able to monitor the performance of the PV string according to various conditions as efficiently as possible and accurate.
Keywords: Box plot method; Solar farm; Solid state transformer